Spatial branching in random environments and with interaction - Englander, Janos (Advanced series on statistical science & applied probability, 2015)
This unique volume discusses some recent developments in the theory of spatial branching processes and superprocesses, with special emphasis on spines, laws of large lumbers, interactions and random media. Although this book is mainly written for mathematicians, the models discussed are relevant to certain models in population biology, and are thus hopefully interesting to the applied mathematician/biologist as well. The necessary background material in probability and analysis is provided in a comprehensive introductory chapter. Historical notes and several exercises are provided to complement each chapter